Effects of Naringenin and Its Glycosides on Functional Properties of Oat Protein and Their Interaction Mechanism - Wuzhen LIU; Ti LI; Qin GENG; Jun CHEN; Jialong HAN; Chengmei LIU; Taotao DAI (Shipin gongye ke-ji)
To investigate the effect of naringenin and its glycoside (naringin and narirutin) on foaming, emulsifying and interfacial tension of oat protein and their interaction mechanism, in this study, fluorescence spectra and circular dichroism were used to elucidate the interaction mechanism and protein structure changes of oat protein-flavonoid complex system. The interaction of oat protein-flavonoid complex system was visualized by molecular simulation technique. The results showed that naringenin, naringin, and narirutin significantly improved the foaming and emulsifying properties of oat protein, and reduced the interfacial tension of oat protein, and the effect of glucoside flavonoids was better, namely naringin>narirutin>naringenin. The results of fluorescence and molecular simulation showed that the three flavonoids interact with oat protein mainly through hydrogen bonding and van der Waals force, and the binding constants at room temperature were narirutin (11.05×104 L/mol)>naringenin (6.25×104 L/mol)>naringin (0.23×104 L/mol). The three flavonoids changed the tertiary structure (fluorescence spectral redshift), secondary structure (α-helix decreased, β-folding and random curling increased), and decreased surface hydrophobicity of oat protein, which resulted the and functional properties (foaming and emulsification) of oat protein improved. These results can provide a theoretical reference for selecting suitable flavonoids for oat protein-based products.